A point absorber wave energy converter with nonlinear hardening spring power-take-off systems in regular waves. (November 2020) - Zheng, Zhongqiang; Yao, Zhipeng; Chang, Zongyu; Yao, Tao; Liu, Bo
Point absorber wave energy converter is one of the most effective wave energy harness devices. Most of the wave energy converters generate energy by oscillating the floating body. Usually, the power-take-off system is simplified as a linear spring and a linear damper. However, the narrow frequency bandwidth around a particular resonant frequency is not suitable for real vibrations applications. Thus, a nonlinear hardening spring and a linear damper are applied in the power-take-off system. The bandwidth of hardening mechanism is discussed. The dynamic model of wave energy converter is built in regular waves with time domain method. The results show that the nonlinear wave energy converter has higher conversion efficiency than the linear wave energy converter more than the natural frequency state. The conversion efficiency of the nonlinear wave energy converter in the low frequency state is closed to the linear converter. The amplitude of the incident wave, the damping of the nonlinear wave energy converter and the nonlinear parameterα affect the energy capture performance of the wave energy converter.